2011
DOI: 10.4314/bjpm.v12i1.63387
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the utilization of antenatal care services in Ibadan, Nigeria

Abstract: BACKGROUND:Antenatal care utilization is still low in Nigeria. This underutilization varies from region to region and from state to state. This study assesses the factors that determine the utilization of antenatal care service in Ibadan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
71
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(110 citation statements)
references
References 2 publications
25
71
7
Order By: Relevance
“…More than 90% of women declared that the importance of HIV testing in pregnancy, nutrition during pregnancy, medicines that are safe to take during pregnancy and how to take care of a newborn baby were discussed during ANC. These results are similar to those found by Dairo and Owoyokun in Ibadan [18], Oladapo et al [27] in South Western Nigeria where 97.1% and 85.6% of women respectively who attended ANC received similar information. On the contrary, Gross et al found that in the Kilombere valley, South Eastern Tanzania only 19% of women had information on the appropriate diet in pregnancy, meanwhile 28% had HIV counselling and 3% had information on medicines safe to use in pregnancy [28].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…More than 90% of women declared that the importance of HIV testing in pregnancy, nutrition during pregnancy, medicines that are safe to take during pregnancy and how to take care of a newborn baby were discussed during ANC. These results are similar to those found by Dairo and Owoyokun in Ibadan [18], Oladapo et al [27] in South Western Nigeria where 97.1% and 85.6% of women respectively who attended ANC received similar information. On the contrary, Gross et al found that in the Kilombere valley, South Eastern Tanzania only 19% of women had information on the appropriate diet in pregnancy, meanwhile 28% had HIV counselling and 3% had information on medicines safe to use in pregnancy [28].…”
Section: Discussionsupporting
confidence: 81%
“…This corroborates the findings of the DHS 2004 in which only 48.4% of rural women had four or more ANC visits against 78.4% for urban women [17]. Dairo and Owoyokun [18] found that women from the rural parts of Ibadan were less likely to attend ANC than women in urban settings.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…More than fifty percent 144(53%) respondents received ANC services from upazilla health complex/government hospital and 127(47%) respondents received ANC services from non government organization(private clinic, provincial hospital, health centre and NGO clinic). This finding was consistent with the study finding conducted in Tangail district of Bangladesh 14 and study conducted in Nigeria 19 . The study done in rural area of Punjab noted that 625 (66.1%) of the respondents reported of home delivery and 320 (33.9%) reported of institutional delivery 20 .…”
Section: Recommendationsupporting
confidence: 83%
“…So far, the utilization of antenatal care services in developing countries was less (65%) than developed countries (97%). [3] In Indonesia, utilization of antenatal care in healthcare professionals was just 61.4%. [4] Factors that influence the utilization of antenatal care are the kind of residence area (city or rural), age, the number of births or parity, education level, and wealth or economic status.…”
Section: Introductionmentioning
confidence: 99%